ANALYSIS OF FINANCIAL FEASIBILITY OF BAMBANG LANANG WOOD IN RANTAU PANJANG VILLAGE BUAY RAWAN DISTRICT SOUTH OKU REGENCY - Bachri, Samsul; Purba, Yudhi Zuriah Wirya; Saleh, Wardi (Journal of Agri Socio Economics and Business, 2024)
The aim of this research is to analyze the financial feasibility of bambang lanang wood farming and the factors that influence it in Rantau Panjang Village, Buay Rawan District, South OKU Regency, South Sumatra Province. The research method used in this research is a survey, using a questionnaire as a data collection tool. The sampling of sample farmers was carried out at simple random (simple random sampling), namely 25 sample farmers from 205 members of the population. The data used is primary data and secondary data. Based on the research results, it can be concluded that the Bambang Lanang wood farming business is worth cultivating with a Net Present Value (NPV) of Rp. 5,210,716,-/Ha, Net Benefit Cost Ratio (Net B/C) of 2.24, Gross Benefit Cost Ratio (Gross B/C) of 2.22 and Internal Rate of Return (IRR) of 19.07%, Return On Investment (ROI) of 609.17% and Payback Period (PP) of 2.12 years. Meanwhile, the Switching Value Analysis results were 55.05% with the influencing variables namely selling price (Rp.) and production quantity (M3) decreasing to NPV=0